MENINGKATKAN AKSESIBILITAS PEMILIH DISABILITAS DALAM PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH MELALUI PENDIDIKAN DAN KESADARAN - Mahin, Mikael (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Abstract: Political participation is a constitutional right of every citizen, including persons with disabilities. In Sintang Regency, West Kalimantan, accessibility challenges for voters with disabilities remain significant, particularly in voter education and public awareness. This study aims to analyze the extent to which education and public awareness can improve accessibility for voters with disabilities in regional elections (Pilkada). This study used a descriptive qualitative approach. The research location was Sintang Regency, which has already held regional elections. Data collection techniques included: in-depth interviews with persons with disabilities, election organizers, and disability organizations; observation of election simulations for persons with disabilities; and documentation study of policies and election participation reports from the Sintang General Elections Commission (KPU). Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results indicate that limited information, lack of involvement of disability groups, and social stigma are the main obstacles. The implementation of adaptive voter education and public awareness campaigns can increase the participation and empowerment of voters with disabilities. This study suggests the need for an integrated strategy among stakeholders to achieve inclusive and equal elections in Sintang Regency. Keywords: Accessibility, voters with disabilities, voter education, public awareness.